The Influence of Individual Characteristics towards the Use of Social Media as a Learning Tool: An Empirical Analysis - Ali, Murad; Yaacob, Raja Ahmad Iskandar Bin Raja; Endut, Mohd Nuri-Al-Amin B. (International Review of Management and Marketing, 2017)
The advent of social media has significantly changed the entire landscape of information accessing and sharing which is more horizontal, single tired and with multilateral manner. This platform empowered every individual to create, access interact, and share their information online. This fast-growing use of these applications in a short period of time is because of youth and students and can facilitate them in different types of communication and learning. However, students considered these applications as a source of entertainment and use it substantially for their social interaction. This attitude of Young's and students has turned these facilities into a source of distraction, which diverts their attention from their effective learning. The prior research has formally declared that social media have the potential to improve student learning and academic activities, even though, less effort has been made to know the student's perception of these applications for learning purposes. The current study has been carried out with the objective to inquired student's psychological characteristics in respect to the acceptance of these applications for learning purposes. Data for this current research was collected from top five research universities Malaysia. Applying Big Five Framework of McCrae & Costa, (1987) as a theoretical approach, our finding shows that student's psychological characteristics are positively and significantly affect their use of social media application for learning and academic purposes. Furthermore, future directions are also suggested. Keywords: Individual characteristics, Personality, Social Media, Social Learning, Information Sharing JEL Classification: D83